Influence of Nitrobenzene and Acetonitrile in p-Chloroaniline and 1,4-dioxane - Bakkialakshmi, S.; Shanthi, B.; Santhi, R.; Chandrakala, D. (Asian Journal of Chemistry, 2016)
An attempt has been made to obtain the fluorescence quenching spectra of p-chloroaniline using nitrobenzene and acetonitrile, as quenchers in 1,4-dioxane. The concentration of fluorescer solution was kept constant (0.01 m) in each experiment, by adding fixed aliquot of stock solutions prepared in the solvent. Quenchers (nitrobenzene and acetonitrile) in the respective solvent was added to the above solution in small volumes (0.1–0.5 mL) and the fluorescent intensities were measured. The Stern-Volmer constants for all quenching processes were plotted. Regression analysis for Stern-Volmer plot was carried out. Regression coefficient and the Stern-Volmer constant were calculated. Stoke's shift, ionization potential, electron affinity and the solvent parameter were also calculated.